THE TOXICITY OF METHANOL EXTRACT OF MAULI BANANA STEM (Musa acuminata) AGAINST BONE MARROW MESENCHYMAL STEM CELL IN VITRO - Amy Nindia Carabelly; Suhartono Taat Putra; Ketut Suardita (FKG Unlam, 2017)
ABSTRACTThe latest regeneration therapy has developed towards the usage of Mesenchymal stem cells (MSC) including for aggressive periodontitis, but limited amounts of MSC need extra growth factor in cells culture process. Growth factor is quite expensive so an alternative source is needed. Mauli banana stem is a proven antioxidant and has the most bioactive tannin. Methanol extract of mauli banana stem is not toxic towards fibroblast cell BHK 21 with 25% concentrate, but there is no research about the toxicity of methanol extract of mauli banana stem against MSC. Purpose: To analyze the toxicity of methanol extract of mauli banana stem against MSC in vitro. Method and source: True experimental using the posttest only control group design. MSC culture with treatment methanol extract of mauli banana stem with dosage 2,5 mg/ml; 5 mg/ml; 7,5 mg/ml; 10 mg/ml. Treatment Con A5 μg/ml is used for positive control group and is not treated as negative control group. Each group is incubated for 24 hours and 48 hours, then it is given reagent MTT and is read with ELISA reader. Result: Kruskal-Wallis and independent-sample T-test result shows that there is a significant difference between treatment group and control group. Conclusion: Methanol extract of mauli banana stem with dosage 2.5 mg/ml; 5 mg/ml; 7.5 mg/ml; 10 mg/ml is toxic towards MSC in vitro under treatment for 24 hours and 48 hours.Key words : Mauli banana stem, Mesenchymal stem cells, Toxicity